ENVIRONMENTAL CONDITIONS ON THE INCIDENCE OF STUNTING IN SIAU DALAM VILLAGE, JAMBI - Fitria Eka Putri; Rika Gusna Dewi; Rumita Ena Sari; Fajrina Hidayati; Evy Wisudariani; Hubaybah Hubaybah (Lembaga Pengembangan Kinerja Dosen, 2023)
Global data for 2018 shows that 149 million children worldwide or the proportion of toddlers experiencing stunting is 21.9%. The incidence of recurrent infectious diseases is a direct factor causing stunting, where this factor is closely related to unsanitary sanitation conditions and the behavior of washing hands with soap. This research was conducted with the aim of finding the relationship between washing hands with soap, clean water facilities and ownership of healthy latrines with the incidence of stunting in toddlers. This study used an analytic observational design and a cross-sectional approach. The sampling technique used random sampling with a total of 100 samples. Data were collected directly from respondents through interviews and observations using questionnaires and observation sheets. Data were analyzed using the chi square test. The results of the study found that there was a relationship between clean water facilities and the incidence of stunting in Siau Dalam Village, with a p value = 0.000. There is no relationship between ownership of healthy latrines and the incidence of stunting in Siau Dalam Village with a p value = 0.115. It is hoped that the puskesmas will be more active in role health education with creative methods related to making and utilizing healthy latrines and it is important to use clean water which are aspects that are considered in the triggering factors for stunting. Keywords: Stunting, clean water facilities, Letrine.